Analisis Keputusan Pemerintah Kanada dalam Mengadopsi United Nations Declarations on the Rights of Indigenous People (UNDRIP) Pada Tahun 2016 - Somadianti, Luthfiyya Tsana; Pattipeilohy, Shary Charlotte Henriette (Journal of International Relations, 2021)
In 2016, Canada announced that they will implement the United Nations Declarations on the Rights of Indigenous People (UNDRIP) during the United Nations General Assembly. It is widely known that Canada is home to indigenous communities that consisted of inuit, metis and first nations people. The Canadian government also regulate the lives of canada’s indigenous communities through the Indian Act. The announcement made by Canada raised questions such as why suddenly Canada made the decision and announce such decision in front of international stage. Using decision making theory by Snyder, Bruck and Sapin alongside the concept of human rights and identity, the researcher aims to understand what factors that influenced canada to make such decision. This study resulted in the founding of influencing factors divided into internal and external factors. Dominant party, Canada's identity as a multicultural country, and a protest by idle no more movement were the factors that categorized as the internal factors. Meanwhile, pressures from international organizations, the changed stances of the countries that originally share the same views as Canada, pressures from other countries regarding Canada's stance on UNDRIP, and also the global trend on human rights enforcement were the external factors.